Romanian perspectives regarding the inter-war plans of creating a "Danubian Confederation"; Perspecti ve româneşti cu privire la planurile interbelice de creare a unei "Confederaţii Dunărene" - Mihai Sebe (European Institute of Romania, 2011)
The purpose of the current paper is to undergo a synthetic examination of the evolution of the Danube issue in inter-war Romania, to realise a synthetic presentation of the Romanian intellectual currents and evolutions, of a history of the plans for a Danubian organisation in the inter-war political and intellectual environment. The paper highlights the preoccupation of the Romanian elites concerning the evolutions on the European scene, by offering solutions and analysing from a scholarly perspective the envisaged propositions. The Romanian conception on the Danube area is characterised by the importance granted to the political aspect - equality of the riparian states, regulation of the regime of navigation, etc. We are dealing with a qualitative evolution that goes from a purely defensive reaction, of denial of the initial plans of Danubian regulation towards a proactive attitude, based upon solving issues and offering plans for organisation.
Keywords: 330; Danubian Confederation; Romania; inter-war period; Danube; Europe; regional construction